2021
DOI: 10.1186/s40545-021-00389-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical policies and regulations of oral antiviral drugs for treatment of hepatitis C in Egypt—case study

Abstract: Background There are limited studies on the role of efficient regulatory mechanisms in facilitating greater access to Hepatitis C virus (HCV) treatment. Evidence to support the importance of effective pharmaceutical policies and regulations in improving access to oral viral drugs towards the elimination of HCV is needed. This study aims to explore the adequacy of the implemented pharmaceutical policies and regulations in Egypt and their role to improve the availability and affordability of dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…5 It has historical precedent as a cost-reduction strategy in the treatment of HIV/AIDS, tuberculosis, and malaria, where pooled procurement was demonstrated to reduce originator and generic prices by 42.4% and 35% respectively, 31 and more recently in the treatment of Hepatitis C, where pooled procurement of direct-acting antivirals reduced prices by up to 99%. 32 Our study observed a potential relationship between increasing purchase volumes and decreasing variance in prices, suggesting that pooled procurement may be beneficial in price stabilization. Pooled procurement has the additional benefits of increasing resiliency of supply chains and reducing quality uncertainty by imposing minimum quality standards.…”
Section: Discussionmentioning
confidence: 58%
“…5 It has historical precedent as a cost-reduction strategy in the treatment of HIV/AIDS, tuberculosis, and malaria, where pooled procurement was demonstrated to reduce originator and generic prices by 42.4% and 35% respectively, 31 and more recently in the treatment of Hepatitis C, where pooled procurement of direct-acting antivirals reduced prices by up to 99%. 32 Our study observed a potential relationship between increasing purchase volumes and decreasing variance in prices, suggesting that pooled procurement may be beneficial in price stabilization. Pooled procurement has the additional benefits of increasing resiliency of supply chains and reducing quality uncertainty by imposing minimum quality standards.…”
Section: Discussionmentioning
confidence: 58%